2022
DOI: 10.3389/fcell.2022.884590
|View full text |Cite
|
Sign up to set email alerts
|

Novel prognostic matrisome-related gene signature of head and neck squamous cell carcinoma

Abstract: Background: Head and neck squamous cell carcinoma (HNSCC) is a common malignancy of the mucosal epithelium of the oral cavity, pharynx, and larynx. Laryngeal squamous cell carcinoma (LSCC) and oral squamous cell carcinoma are common HNSCC subtypes. Patients with metastatic HNSCC have a poor prognosis. Therefore, identifying molecular markers for the development and progression of HNSCC is essential for improving early diagnosis and predicting patient outcomes.Methods: Gene expression RNA-Seq data and patient c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 61 publications
1
3
0
Order By: Relevance
“…LAMB4 belongs to the laminin family, constituents of the extracellular matrix, however it is still poorly characterized, and it is currently not known to take part into any laminin heterotrimers 26,27 . The only study on its relation to migration reported that LAMB4 silencing in head and neck squamous cell carcinoma promotes migration, in agreement with what we found in fibroblasts 28 . GORASP1, also known as GRASP65, is a Golgi structural protein critical in establishing polarity in migrating cells once regulated by phosphorylation 29 .…”
Section: Hit Analysis Confirms Known Migration-related Genessupporting
confidence: 91%
“…LAMB4 belongs to the laminin family, constituents of the extracellular matrix, however it is still poorly characterized, and it is currently not known to take part into any laminin heterotrimers 26,27 . The only study on its relation to migration reported that LAMB4 silencing in head and neck squamous cell carcinoma promotes migration, in agreement with what we found in fibroblasts 28 . GORASP1, also known as GRASP65, is a Golgi structural protein critical in establishing polarity in migrating cells once regulated by phosphorylation 29 .…”
Section: Hit Analysis Confirms Known Migration-related Genessupporting
confidence: 91%
“…Furthermore, we compared the previous GPCR-based model with other models from previous studies. 23 , 24 , 25 , 26 As indicated by C-index comparison, the GPCR-based model outperformed them in predicting OS for HNSCC patients ( Figure S4 ). Moreover, we constructed a nomogram based on GPR87, S1PR4, and S1PR5 expressions ( Figure 4 D).…”
Section: Resultsmentioning
confidence: 88%
“…Huang et al determined that LAMB4 is overexpressed in head and neck squamous cell carcinoma, and knockdown of LAMB4 expression can effectively delay tumor progression. [58] Therefore, it can be inferred that BMGs participate in the regulation of TME, and produce corresponding pathological changes to promote tumor progression. According to this study, the high-risk group with glioma expressed more HLA, immunological checkpoints, chemokines, and chemokine receptors.…”
Section: Discussionmentioning
confidence: 99%